Branding in Crisis: Pizza Hut Indonesia’s Strategic Response to Boycott through Ristorante - Prayudi, Prayudi; Putra, Gilang Septian; Botu, Yehezkiel Ronaldo (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2024)
This study investigates the brand strategy of Pizza Hut Indonesia in response to reputational damage caused by public boycott campaigns related to the Israel–Palestine conflict. The research particularly examines the strategic role of Ristorante, a localized sub-brand introduced following the crisis, in repositioning the brand, redefining its personality, and reconstructing its identity. Employing a qualitative method with a case study approach, the study draws from literature reviews, corporate documentation, and media sources to analyze the multidimensional branding strategy implemented. The findings reveal that Ristorante served as a branding innovation aimed at realigning Pizza Hut Indonesia with national values, emotionally engaging Generation Z consumers, and demonstrating empathy through local community involvement. The brand repositioned itself as culturally rooted and emotionally responsive, moving beyond global fast-food narratives to emphasize Indonesian ownership, lifestyle alignment, and corporate social responsibility. This research contributes to brand communication theory by showing how emotional branding, localized innovation, and socio-political sensitivity can serve as key mechanisms in brand recovery and resilience during crises. The study also highlights the importance of embedding empathy, cultural relevance, and consumer values into the core of brand strategy. However, the research is limited to a single case and relies on secondary data, suggesting opportunities for future studies to validate findings through comparative and longitudinal approaches.